ABILITY, MOTIVATION, OPPORTUNITY-ENHANCING HRM PRACTICES AND CORPORATE ENVIRONMENTAL CITIZENSHIP: REVISITING THE MODERATING ROLE OF ORGANISATIONAL LEARNING CAPABILITY IN MALAYSIAN CONSTRUCTION COMPANIES - Tay Lee Chin; Tan Fee Yean; Hon-Wei Leow (International Journal of Business and Society, 2023)
This study examines the connection between ability, motivation, opportunity-enhancing HRM practices and corporate environmental citizenship. Organisational learning capability is also introduced as a moderator between the connections of AMO-enhancing HRM practices and corporate environmental citizenship. Systematic sampling technique was utilized to determine the study sample with a total response of 150. The study found that ability and opportunity-enhancing HRM practices are related to corporate environmental citizenship except for motivation-enhancing HRM practices. Similarly, organisational learning capability has no moderating effect on such relationships. In addition to that, this study has provided a comprehensive understanding of corporate environmental citizenship in the construction industry in Malaysia. This substantially adds a new dimension to the literature.